En-Synthesen (substituierende Additionen) mit Cyansäureester, Isocyansäureestern und Chinonen an nichtbenzoiden Aromaten und Heterozyklen - W. Treibs (CHIMIA)
Ester of the cyanic and isocyanic acids as well as 1,4- and 1,2-quinones perform en-syntheses with azulenes and some heterocycles. These reactions are catalysed by heat, UV-light and Lewis-acids. Some of the reactions-products of the azulenes are easily polarised, visible by changes of colour.